Answer:
A = (2p + 9) (2p - 9)
B = (x - 9) (x - 4)
Step-by-step explanation:
For A : Rewrite 4p^2 as (2p)^2.
(2p)^2−81
Rewrite 81 as 9^2.
(2p)^2−9^2
Since both terms are perfect squares, factor using the difference of squares formula, a^2 − b^2 = ( a + b ) ( a − b ) where a = 2p and b = 9 .
(2p + 9) (2p − 9)
For B : Consider the form x^2 + bx + c . Find a pair of integers whose product is c and whose sum is b . In this case, whose product is 36 and whose sum is − 13 .
-9, -4
(x - 9) (x - 4)
I hope this helps.
Answer:
about 11.50
Step-by-step explanation:
6 / 5.70 = 1.05
1.05 x 11
hope this helps
Only numbers possible would be five and zero
45.019 i believe space filler
Answer:
99 24/25
Step-by-step explanation:
8.33*√144=
8.33*12=99 24/25 or 100 with 8.33 bar